INHIBITING ACTIVITY OF ANGIOTENSIN CONVERTING ENZYME-1 BY BEAN PROTEIN HYDROLYSATE GENUS PHASEOLUS - Tejasari Tejasari; Faiqotul Aulia; Nurdiana Agustina (Jurnal Penelitian Pascapanen Pertanian, 2021)
Kidney bean (Phaseolus.vulgaris L. Chitra) and lima bean (Phaseolus lunatus L. Sweet) hydrolysates were obtained by alcalase and flavourzyme hydrolysis of the bean seed protein. Peptide in the bean hydrolysates, with hydrophobic amino acids had been studied for their inhibitory ACE-1 activity preventing transformation into ACE-2 that prevention hypertension. This study aimed to measure inhibitory ACE-1 activity of protein hydrolyzates from the bean Phaseolus genus spp. grown in Jember, and its solubility. The bean protein (19.8-20,2%) was extracted using isoelectric precipitation at pH 4-4,6. The extract were hydrolyzed at pH 8-9 for alcalase and pH 7 for flavourzyme, followed with inactivation at 80-85 o C. ACE-1 inhibitory activity was measured based on the amount of hippuric acid (HA) formed by the hydrolysis of Hippuryl-His-Leu (HHL) in spectrophotometry detection method (228 nm). The ultra chromatography evaluation showed that the protein hydrolysates of kidney bean contained higher hydrophobic amino acids (455.5 mg/g protein) compare to those of lima bean (350 mg/g protein). Protein hydrolysates of both beans from alcalase hydrolysis have higher ACE-1 inhibitory rather than those from flavourzyme. Protein hydrolysate from Phaseolus spp bean protein hydrolysis by alcalase, contain small molecular weight peptides (3.9-22.6 kDa) high ACE-1 inhibition ability (83 -88%), and therefore suggested as antihypertensive nutraceuticals. Highest solubility of protein hydrolysate resulted from alcalase hydrolysis of both beans were observed at pH 8-9, while those resulted from flavorzyme hydrolysis were at pH 7.